2020
DOI: 10.1136/lupus-2020-000395
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of hydroxychloroquine dose adjustment according to the American Academy of Ophthalmology guidelines in systemic lupus erythematosus

Abstract: ObjectiveThe American Academy of Ophthalmology recommends a maximum hydroxychloroquine (HCQ) dose of ≤5.0 mg/kg/day to reduce the risk of HCQ-induced retinopathy. To determine if this dose adjustment would have an impact on the clinical course of SLE, we compared outcome measures in a cohort of patients with SLE before and after adjusting HCQ dose.MethodsSixty Puerto Ricans with SLE (per 1997 American College of Rheumatology criteria) treated with HCQ who were changed to HCQ ≤5.0 mg/kg/day were studied. Visits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…They showed no significant differences in disease activity scores, exacerbations, emergency room visits, hospitalizations, and diseaserelated damage from before and 2 years after the change. 41 Of note, this study was limited by its small sample size, limited diversity, and short follow-up. Another case-crossover study looked at 342 patients with SLE from Massachusetts General Hospital in the 5-year period following the 2016 HCQ dosing recommendations and found that HCQ dosing of 5 mg/kg per day or less, in accordance with current guidelines, was associated with a higher risk of lupus flares.…”
Section: Nuances In Clinical Testingmentioning
confidence: 96%
“…They showed no significant differences in disease activity scores, exacerbations, emergency room visits, hospitalizations, and diseaserelated damage from before and 2 years after the change. 41 Of note, this study was limited by its small sample size, limited diversity, and short follow-up. Another case-crossover study looked at 342 patients with SLE from Massachusetts General Hospital in the 5-year period following the 2016 HCQ dosing recommendations and found that HCQ dosing of 5 mg/kg per day or less, in accordance with current guidelines, was associated with a higher risk of lupus flares.…”
Section: Nuances In Clinical Testingmentioning
confidence: 96%
“…Current dosing recommendations of 5 mg/kg/day were developed to mitigate the risk of retinal toxicity rather than to maximise efficacy 59 . The European League Against Rheumatism recommends dose‐reducing patients with long‐standing stable disease 59 with some data suggesting no increased risk of flare when reducing from 6.5 to 5 mg/kg/day 60 . However, recent data raise the question of whether body weight dosing is the ideal method of HCQ dosing.…”
Section: The Bigger Picturementioning
confidence: 99%
“…It is important to emphasize that the studies confirming the effectiveness of HCQ were carried out at the dose of 6.5 mg/kg [38]. Recently, results have been published according to which the use of doses of ≤ 5 mg/kg does not affect the effectiveness of therapy [73]. Taking the currently recommended dose, a person weighing 40 kg, 60 kg, or 80 kg should receive 200 mg, 300 mg, or 400 mg, respectively, of the drug per day.…”
Section: Mechanizm I Efekty Działaniamentioning
confidence: 99%
“…Należy podkreślić, że badania potwierdzające skuteczność HCQ były przeprowadzane przy stosowaniu dawki 6,5 mg/kg [38]. Ostatnio opublikowano jednak wyniki, według których stosowanie dawek ≤ 5 mg/kg nie wpływa na skuteczność terapii [73]. Przyjmując aktualnie rekomendowaną dawkę, w uproszczeniu: osoba ważąca 40 kg powinna otrzymywać 200 mg leku na dobę, osoba ważąca 60 kg -300 mg, a osoba ważąca 80 kg -400 mg. Z uwagi na długi okres półtrwania leku i uwzględniając dostępną gramaturę tabletek zawierających HCQ, w przypadku podawania 300 mg/dobę, sugeruje się schemat naprzemiennego stosowania 400 mg i 200 mg w kolejne dni [3,10].…”
Section: Factors Influencing the Effectiveness Of Treatmentunclassified